Correlation Between Best Corrected Visual Acuity Acquired by Snellen Chart with Potential Visual Acuity of Retinometry in Ametropic Patients - Dera Tresna Utami; Fatimah Dyah NA (Majalah Oftalmologi Indonesia, 2017)
Introduction: Potential vision is determined by assessing macular function. Retinometer is a tool that is often used to assess the potential visual acuity. Refractive error is the most common cause of vision decline. Currently, examination of best visual acuity still uses Snellen chart, but if the result of vision correction with Snellen chart not maximized can cause the emergence of other problems such as amblyopia. Objective: To analyze correlation between best corrected visual acuity (BCVA) acquired by Snellen chart with potential visual acuity of retinometry in ametropic patients. Methods: This was an observational cross sectional study, enrolled at department of ophthalmology dr. Karidi General Hospital. This study involving 73 myopic eyes of 40 patient. After having their potential vision examined with retinometer, patient undergoing visual acuity assesment with Snellen chart. Statistical analysis using Spearman correlation. Result: In this study we found retinometry scale 0,8 for BCVA 1.0 (56,8%) and 0.32 for BCVA < 1.0 (48,4%) as the most common finding respectively. We found most of mild myopia cases in patients with BCVA 1,0 (52%) and high myopia in patients with BCVA < 1.0 (71%). Statistical analysis shows a moderate strength-positive correlation between potential visual acuity retinometry with best corrected visual acuity acquired by Snellen. Conclusion: BCVA acquired by Snellen shows moderate strength-positive correlation with potential visual acuity retinometry in ametropic patient. Scale 0.63 in retinometry can be used as benchmark for predicting visual acuity after correction reach 1.0.